(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
he purpose of the study was to find out the effect of specific yogic practices and resistance training on aggression among male kabaddi players. To achieve the purpose of the present study, sixty inter-collegiate level Kabaddi players were selected as subjects at random from affiliated colleges of Bharathidasan University, Tiruchirappalli, Tamilnadu state, India and their ages ranged from 20 to 25 years. The subjects were divided into three equal groups of twenty each. Experimental Group I was exposed to specific yogic practices, Experimental Group II was exposed to resistance training and Control Group was not exposed to any experimental training other than their regular daily activities. The duration of experimental period was 12 weeks. The pre test and post test scores were subjected to statistical analysis using Analysis of Covariance (ANCOVA) and Scheffe’s post hoc test was used. In all cases 0.05 level of significance was fixed to test hypotheses. The specific yogic practices group showed significant improvement on aggression than the resistance training and control groups.